Experimental optical phase measurement approaching the exact Heisenberg limit - Shakib Daryanoosh (Nature Portfolio, 2018)
Measurements of an unknown optical phase have not yet been performed with the ultimate precision, i.e. saturating the Heisenberg limit. Here, Daryanoosh et al. demonstrate this with a precision within 4% of the Heisenberg limit by combining photonic entanglement and multiple passes.